Giant congenital melanocytic nevi (garment variety): a case report - Singh, Om Prakash; Kumar, Vikas; Kumar, Rahul (International Journal of Contemporary Pediatrics, 2021)
Giant congenital melanocytic nevi (GCMN) are large brown-to-black skin lesions caused due to genetic mutations which lead to defective proliferation, differentiation and migration of melanoblasts which are precursor cells of melanocytes. There is a mutation in the NRAS gene causing abnormal proliferation of embryonic melanoblasts. Congenital melanocytic nevus is primarily a clinical diagnosis. The malignant melanoma and neurocutaneous melanosis are the two major complications associated with GCMN. The risk of transformation of GCMN to malignant melanoma varies between 0 and 3.8%. About 1% of live births presents with a CMN. The incidence of GCMN is estimated at less than 1: 20,000 newborns. The variety ‘garment-like’ of GCMN is even scarcer, 1: 5,00,000. GCMN has got major psychosocial impact on the patient and his family due to its unsightly appearance. Treatment includes surgical and non-surgical procedures, psychological intervention and clinical follow-up, with special attention to changes in color, texture on the surface of the lesion. We presented a case of 1-day-old female neonate born with GCMN in our hospital.